Mild Hyperthermia-Induced Myogenic Differentiation in Skeletal Muscle Cells: Implications for Local Hyperthermic Therapy for Skeletal Muscle Injury - Lee, Hojun (Oxid Med Cell Longev, 2018)
The percutaneous application of controlled temperature on damaged muscle is regarded as a prevalent remedy. However, specific mechanisms are not completely understood. Therefore, cellular behaviors of myoblasts were investigated under a physiological hyperthermic temperature. The myoblasts were cultured under no treatment (NT, 37°C, 24 h/day), intermittent heat treatment (IHT, 39°C, 2 h/day), and continuous heat treatment (CHT, 39°C, 24 h/day) during proliferation, migration, or myogenic differentiation. Although the effects of mild heat on migration were not observed, the proliferation was promoted by both IHT and CHT. The myogenic differentiation was also enhanced in a treatment time-dependent manner, as evidenced by an increase in myotube size and fusion index. The gene expressions of mitochondrial biogenesis (Pgc-1α, Nrf1, and Tfam), a subset of mitochondrial dynamics (Mfn1 and Drp1), and a myogenic regulatory factor (myogenin) were increased in a heat treatment time-dependent manner. Interestingly, the mild heat-induced myogenic differentiation and myogenin expression were retarded significantly in PGC-1α-targeted siRNA-transfected cells, suggesting that mild hyperthermia promotes myogenic differentiation via the modulation of PGC-1α. This study provides cellular evidence supporting that local hyperthermic treatment at 39°C is regarded as an effective therapeutic strategy to promote satellite cell activities in regenerating myofibers.